Antimotivation Determinants of Educational Activity among Pedagogical University Students. (5th December 2015) - Ivanova, Natalia; Minaeva, Elena
Abstract: The paper deals with studying the most relevant environmental antimotivation determinants of educational activity in pedagogical university students. An original questionnaire on antimotivation in educational activity designed for students and developed on the basis of the environmental approach for pedagogical higher education institutions is represented in the article. The components of educational environment are considered as environmental antimotivation determinants of educational activity in pedagogical university students: spatial and objective one, psychodidactic, social and subjective components, as well as microenvironment (the family environment) and macroenvironment (society as a whole). According to the results of research, the psycho-didactic component of the educational environment of a higher education institution has been found to be a statistically more pronounced antimotivation determinant of educational activity in pedagogical university students. It has been proved that all environmental antimotivation determinants of educational activity singled out in students are in direct correlation dependence. For respondents, educational activity antimotives conditioned by psycho-didactic component of the educational environment of the university are of uniform significance, which has been determined on the basis of dispersion calculation.